Determinants of Local Governments’ transparency in times of crisis: evidence from municipality-level panel data - Tejedo-Romero, Francisca (2018)
The crisis has impact on Local Government forcing it to be more transparent in management of public resources. This article examines theoretically and empirically the determinants of the levels of transparency in Local Governments based on the agency and legitimacy theories. For the purpose of this study, the analysis is based on the Spanish municipalities over a period of 4 years, between 2008 and 2012. Running a random effect panel data model, our results showed that transparency is associated with economic and political factors. Unemployment rate, gender, electoral turnout, and political strength have a significant effect on the level of transparency. For other variables like investment and fiscal pressure, we did not find significant evidence of their effect on the level of transparency. We conclude that the factors that best explain the variation in the level of transparency in the period of crisis are associated with political factors.